Candida species and selected behavioral factors co-associated with severe early childhood caries: Case-control study - Cvanova, Michaela; Ruzicka, Filip; Kukletova, Martina; Lipovy, Bretislav; Gachova, Daniela; Izakovicova Holla, Lydie; Danek, Zdenek; Hola, Veronika; Bartosova, Michaela; Jarkovsky, Jiri; Dusek, Ladislav; Borilova Linhartova, Petra (Frontiers in Cellular and Infection Microbiology, 2022)
Severe Early Childhood Caries (sECC) is a multifactorial disease associated with the occurrence of specific oral microorganisms and other environmental, behavioral, and genetic factors. This study aimed to construct a multivariable model including the occurrence of Candida spp. and selected behavioral factors (length of breastfeeding, serving sweet beverages and beginning of brushing child’s teeth) to determine their relationships to the occurrence of sECC. In this case-control study 164 children with sECC and 147 children without dental caries were included. MALDI-TOF MS and multiplex qPCR were used to identify Candida spp. and selected bacteria in dental plaque samples, respectively. A questionnaire on oral hygiene, diet, and children’s health was filled in by the parents. The constructed multivariable logistic regression model showed an independent influence of the microbial and behavioral factors in sECC etiopathogenesis. The occurrence of C. albicans and C. dubliniensis was associated with higher odds of sECC development (odds ratio, OR: 9.62 and 16.93, respectively), together with breastfeeding of 6 months or less (OR: 2.71), exposure to sweet beverages (OR: 3.77), and starting to brush child’s teeth after the 12th month of age (OR: 4.10), all statistically significant (p < 0.01). Considering the high occurrence of C. albicans and C. dubliniensis in dental plaque in children with sECC, we propose them as “keystone pathogens” and risk factors for sECC. The models showed that presence of specific species of Candida in dental plaque may be a better descriptor of sECC than the mentioned behavioral factors.